Prediksi Financial Distress Menggunakan Model Artificial Neural Network pada Perusahaan Perhotelan yang Terdaftar di BEI Tahun 2017-2021 - Natasya Salsabila Nafis; Farida Titik Kristanti; Hanif Kurniawan Atmanto (Universitas Batanghari Jambi, 2023)
This study aims to determine early warning models, differences in calculation results, and prediction results of financial distress using the Artificial Neural Network (ANN) model on data testing of hotel industry companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. In this study, researchers used quantitative research methods where the results obtained from this study were in the form of numbers or data whose values were numbered. The population in this study are companiesÂ Hotels, Resorts & Cruise LinesÂ which are listed on the Indonesia Stock Exchange in 2017-2021 with a total of 17 companies. The data processing procedure in this study begins with calculating financial ratios using Microsoft Excel, then analyzing descriptive statistics, and testing the artificial neural network model using the PYTHON programming language to predict financial distress conditions in companies.